گرنگی ئابووری و ژینگەیی په‌رەپێدانی بەردەوامی گازی سروشتی لە هەرێمی کوردستان (توێژینەوەی هەڵێنجراو) - نه‌قشبه‌ندی, ئازاد محمدامین كاكه‌شێخ; بێده‌ری, پشتیوان جواد أحمد (Sulaimani Journal for Humanities, 2023)
The main objectives of this study are to assess the economical geography of the natural gas of the Kurdistan Region and to identify the capabilities and obstacles to sustainable development in order to determine the main types of sustainable development for the Kurdistan Region. There are two main types of natural gas in the Kurdistan Region: the first is free natural gas, which has been discovered in (10) ten fields of this type of gas in the Kurdistan Region. The second is oil-associated natural gas fields, which natural gas combined with oil is found in several fields in the Kurdistan Region. This study aims to highlight the importance of sustainable economic and environmental development of natural gas in the Kurdistan Region. The importance of the research lies in the fact that the issue of sustainable development of new natural gas and there is little writing about it, based on the descriptive approach to the topics and topics that are discussed, finally, we concluded that Among the quantity, type and reserves of gas, it played the greatest role in providing the energy needed to generate electricity in the region by (80%), which reduced greenhouse gas emissions by (25%.(